System Integrated Digital Empowering and teleRehabilitation to promote patient Activation and well-Being in chronic disabilities: A usability and acceptability study - Rossetto, Federica; Borgnis, Francesca; Isernia, Sara; Foglia, Emanuela; Garagiola, Elisabetta; Realdon, Olivia; Baglio, Francesca (Frontiers in Public Health, 2023)
Introduction Telerehabilitation systems represent a promising way for the management of chronic disability, delivering technology-enabled rehabilitation outside the hospital setting. However, usability and acceptability assessment with users represents a critical starting point when using digital healthcare solutions. This study aims at evaluating the user experience with a Telerehabilitation system (SIDERA∧B) from the end-user side. Methods SIDERA∧B consists of an asynchronous delivery of rehabilitation activities through multimedia digital contents and tele-monitoring of vital parameters with technological devices for individualized, home-based management of chronic conditions. Usability (with the System Usability Scale, SUS) and acceptability (using the Technology Acceptance Model, TAM - and The Service User Technology Acceptance Questionnaire, SUTAQ) data were analyzed from the dataset of the SIDERA∧B project (N = 112 patients with Chronic Heart Failure, Parkinson's Disease and Chronic Obstructive Pulmonary Disease). The possible influence of five external factors (i.e., technological expertise, education, sex, age, and level of disability) on TAM domains was tested using Spearman's Correlation analysis. Results Results showed a satisfactory level of technological usability (SUS Median = 77.5) and good scores in usability and learnability SUS subdomains (mean scores > 2.5). Regarding technological acceptability, participants showed high scores (Median > 4) in “Behavioral Intention”, “Perceived Usefulness”, and “Perceived Ease of Use” TAM domains. Finally, results from the SUTAQ scale highlighted that the SIDERA∧B system obtained optimal scores in all domains, especially in “Increased accessibility,” “Care personnel concerns,” and “Satisfaction.” Age (rho = −0.291, p = 0.002) and disability level (WHODAS Total score: rho = −0.218, p = 0.021) were the two external factors inversely associated with the Perceived Ease of Use. Discussion The age of digital transformation requires everyone to understand, accept and master the changes affecting modern-day healthcare. The usability and acceptability of the SIDERA∧B system were high across all end-users, despite the medium-low level of the technological expertise of the sample. These findings support the efficiency and the suitability of these digital solutions in the modern digital age transition of rehabilitation from inside to outside the clinic.